2015
DOI: 10.1002/ajmg.a.37130
|View full text |Cite
|
Sign up to set email alerts
|

A de novo Mutation in KMT2A (MLL) in monozygotic twins with Wiedemann–Steiner Syndrome

Abstract: Growth deficiency, psychomotor delay, and facial dysmorphism was originally described in a male patient in 1989 by Wiedemann et al. and later in 2000 by Steiner et al. Wiedemann-Steiner syndrome (WSS) has since been described only a few times in the literature, with the phenotypic spectrum both expanding and becoming more delineated with each patient reported. We report on the clinical and molecular features of monozygotic twins with a de novo mutation in KMT2A. Single nucleotide polymorphism (SNP) microarray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
2
14
1
1
Order By: Relevance
“…A trio‐based WES analysis identified a novel de novo missense variant in KMT2A , leading to a molecular diagnosis of WSS. Consistent with the identified molecular lesion, several of the features observed in the proband had been variably reported in patients with KMT2A mutations [Koenig et al, ; Jones et al, ; Mendelsohn et al, ; Strom et al, ; Dunkerton et al, ; Miyake et al, ], and overall fit the condition originally reported by Wiedemann et al [] and Steiner and Marques []. So far, 17 subjects with mutations in KMT2A gene have been reported (Table ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A trio‐based WES analysis identified a novel de novo missense variant in KMT2A , leading to a molecular diagnosis of WSS. Consistent with the identified molecular lesion, several of the features observed in the proband had been variably reported in patients with KMT2A mutations [Koenig et al, ; Jones et al, ; Mendelsohn et al, ; Strom et al, ; Dunkerton et al, ; Miyake et al, ], and overall fit the condition originally reported by Wiedemann et al [] and Steiner and Marques []. So far, 17 subjects with mutations in KMT2A gene have been reported (Table ).…”
Section: Discussionsupporting
confidence: 80%
“…Of note, predisposition to frequent urinary tract infections [Mendelsohn et al, ; Strom et al, ], periodic respiratory infections [Koenig et al, ], and recurrent otitis media [Miyake et al, ] have previously been reported in patients with KMT2A mutations, which supports the view of compromised immunological function in these patients. Similarly, previous reports documented internal organ involvement, which however, were restricted to renal malformation and function [Jones et al, ; Mendelsohn et al, ; Dunkerton et al, ] and cardiovascular abnormalities [Miyake et al, ].…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, seizures an unfrequented sign in WSS was observed in the patient carrying the c.3460C>T (p.(Arg1154Trp)) variant and in only three previously reported individuals (1/3 carrying a CXXC variant and 2/24 carrying another KMT2A variant) [16,21,25]. This patient presented also with cardiac abnormalities as previously observed in five WSS patients and abnormal dentition [7,[18][19][20]. Previous reports showed abnormal dentitions including hypodontia in five WSS patients (2/3 carrying a CXXC variant and 3/24 carrying another KMT2A variant) [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 78%
“…In these five patients the KMT2A variants were predicted to result in premature termination of translation and to a nonsensemediated decay (NMD) of the corresponding transcripts [7]. Since this first description additional WSS patients, including a pair of monozygotic twins, have been reported, especially by using exome analysis approaches, bringing to more than 25 the total number of patients carrying KMT2A variants leading to a premature stop codon [7,[16][17][18][19][20][21][22][23][24][25][26]. KMT2A missense variants have been reported in five patients with WSS, one of them having a severe form of the disease and congenital immunodeficiency [16].…”
Section: Introductionmentioning
confidence: 99%
“…This domain plays a role in methylatransferase activity on histone H3 lysine 4 (H3K4), being able to mono‐ di‐ or tri‐methylation (Wiersma et al, ). Mutations in KMT2A were identified in individuals with Wiedemann–Steiner syndrome, which leads a developmental disorder including ID, microcephaly, short stature and autism features (Dunkerton et al, ).…”
Section: Setd5 Syndrome As a Chromatinopathy Disordermentioning
confidence: 99%